PENGARUH PENDIDIKAN PELATIHAN (DIKLAT), DISIPLIN KERJA DAN PENGALAMAN KERJATERHADAP KINERJA KARYAWAN SECURITY YANG DI MEDIASI RELIGIUSITAS PADA PT. SIGER PERKASA - Rahmat, Rahmat Robani; Habibi, Ahmad; Kurniawan, Muhammad (AT TARIIZ : Jurnal Ekonomi dan Bisnis Islam, 2025)
The purpose of this research is to analyze the influence of training education (diklat), work discipline, and work experience on employee performance with religiosity as an intervening variable The sample in this study consisted of 100 respondents. The sampling technique is simple random sampling. The data analysis technique used SmartPLS 4. The research results show that training and education have a positive and significant effect on employee performance with, work discipline has a positive and significant effect on employee performance and work experience has a positive and significant effect on employee performance. In the data analysis, it turns out that religiosity can mediate the influence of education and training (Diklat), work discipline, and work experience on employee performance with. Religiosity refers to a person's adherence to religious commands, manifested in values such as honesty, discipline, perseverance, and humility, which encourage individuals to work with integrity.